Capturing the power options smile by an additive two-factor model for overlapping futures prices - Marco Piccirilli; Maren Diane Schmeck; Tiziano Vargiolu (Bielefeld University, Center for Mathematical Economics (IMW), 2019)
In this paper we introduce an additive two-factor model for electricity futures prices based on Normal Inverse Gaussian Lévy processes, that fulfills a no-overlapping-arbitrage (NOA) condition. We compute European option prices by Fourier transform methods, introduce a specific calibration procedure that takes into account no-arbitrage constraints and fit the model to power option settlement prices of the European Energy Exchange (EEX). We show that our model is able to reproduce the different levels and shapes of the implied volatility (IV) profiles displayed by options with a variety of delivery periods.
urn:nbn:de:0070-pub-29377564
Keywords: C13; C14; C32; Q40; G13; 330; Volatility Smile; Overlapping Delivery Periods; Arbitrage; AdditiveModels; Power Options; FFT